Pennies from Heaven Based on the Book by Dennis Potter - Potter, Dennis (BBC Worldwide, 2004)
A married sheet music salesman has an affair with a young schoolteacher who becomes pregnant. She runs away and he gives up everything to track her down ... [www.dvd-galaxis.de]